Re-Imagining Asian Religious Identity: Towards a Critical Pedagogy of Religion and Race in Australian Schools - Rod Neilsen; Ruth Arber; Michiko Weinmann (MDPI AG, 2017)
This paper is drawn from a research project that investigates the relationship between teachers' understanding of the religious identity of Asian background students, and recent Australian curriculum initiatives focused on religion and religious identification. Based on responses from an Australia-wide survey, and follow-up interviews from teachers and principals in several Australian states, the project examined the ways that Australian teachers understand, respond to and talk about the religious identities of their students, and the implications of these demands for teacher practice and education. This paper is concerned with the findings from the interview phase that for a significant number of teachers, notions of religion were often elided with culture and race, and often subsumed by broader notions of a nominal 'white' Australian culture. Research conversations appeared framed by an often Christian perspective and sense of self, as opposed to a putative and Asian religious and cultural other. We argue that a better understanding of the ways that teachers participate in discourses of representations about Asian religious identities negotiated by Australian diasporic communities has direct implications for the refinement of policy and for teacher professional learning. In the light of our findings, we further argue that there is a need for curriculum, teachers and researchers to move beyond an understanding of culture and identity that is based on monolingual, monocultural and Anglocentric perspectives that frame the foreign as the 'exotic' other, and define it through references to limited, tokenistic artefacts of culture, which are reinforced by iconic use of language to talk about culture, religion and identity.